EVALUASI PRODUKSI ORTOFOTO SEJATI DARI SFM FOTOGRAMETRI - Aulia Rachmah, Hazizah
Orthophoto is a picture that presents objects on the surface of the earth where projections on previously central objects have been projected orthogonally so that they are equivalent to line maps. However, in orthophoto, there are still some problems because of the existence of objects that are distorted from their proper location and the presence of shadows on an object that can affect the appearance of the orthophoto. This is due to the shifts in relief for erect surfaces such as building walls, tree trunks and so on. To overcome this, a true orthophoto was made. A true orthophoto is the result of the digital rectification process using surface elements in the height model in the orthogonal projection process. In this study, true orthophoto SfM photogrammetry will be compared with true orthophoto using altitude data from LiDAR (orthoimage LiDAR), so an evaluation of true orthophoto SfM photogrammetry and LiDAR orthoimage is obtained. The data used in this study are aerial photographs from non-metric cameras in the form of aerial photographs taken upright and aerial photographs were taken at an angle (tilted) and LiDAR data in the form of point clouds. The study area was conducted in Sewu Temple, Klaten Regency, Central Java Province. Through this research, it is known that orthophoto results from SfM photogrammetry are better quality than orthoimage LiDAR. This can be seen from the results of the comparison of the difference in coordinates at the points observed in each orthophoto product. The distance of the observed point shift is also calculated from each point. The results show that orthophoto from upright aerial photography is good enough against the reference, which is orthophoto from the combination of upright and tilted aerial photographs. In the tested results, the difference value for the X coordinate is greatest at 0.086 meters at the 8th point, while for the smallest X coordinate difference is 0.002 meters at the 21st point. The largest Y coordinate difference value is 0.103 meters at the 11th point and the smallest Y coordinate difference is -0.002 meters at the 4th point. As well as the shifting point being tested between 0.003 meters - 0.103 meters.